DETERMINAN KINERJA ISLAMI: ANALISIS PENGARUH PELATIHAN, PENGEMBANGAN, DAN KUALITAS SUMBER DAYA INSANI PADA KARYAWAN KOPPONTREN AUSATH DARUSSALAM BLOKAGUNG - Mira Ustanti; Rio Septiawan (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study aims to determine the effect of Training, Development, and the Quality of Islamic Human Resources on the Islamic Performance of employees at Koppontren Ausath Darussalam Blokagung, Banyuwangi, both partially and simultaneously. This study focuses on the ecosystem of pesantren cooperatives, which possesses unique sociological and spiritual-cultural characteristics, whereas previous studies have generally focused on Islamic banking. The novelty of this research lies in the use of the Islamic Performance instrument which specifically evaluates the indicators of itqan, ihsan, and mujahadah in the Islamic boarding school environment. The type of research used is explanatory quantitative research. The sampling technique used the simple random sampling method involving 58 respondents. Data collection was carried out using a Likert scale questionnaire. Data analysis was performed with instrument tests, classical assumption tests, and multiple linear regression tests using SPSS software. The results showed that training partially had no significant effect on Islamic performance, while development and the quality of Islamic Human Resources had a significant effect. Simultaneously, the three variables have a significant influence on Islamic performance. These findings conclude that improving performance breathing Islamic values is more effectively achieved through long-term development programs and apparatus integrity rather than mere technical training. The practical implication of this research recommends that Koppontren managers integrate spiritual content in every operational training curriculum.